4x+3(-3x+13)=89

Simple and best practice solution for 4x+3(-3x+13)=89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3(-3x+13)=89 equation:


Simplifying
4x + 3(-3x + 13) = 89

Reorder the terms:
4x + 3(13 + -3x) = 89
4x + (13 * 3 + -3x * 3) = 89
4x + (39 + -9x) = 89

Reorder the terms:
39 + 4x + -9x = 89

Combine like terms: 4x + -9x = -5x
39 + -5x = 89

Solving
39 + -5x = 89

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-39' to each side of the equation.
39 + -39 + -5x = 89 + -39

Combine like terms: 39 + -39 = 0
0 + -5x = 89 + -39
-5x = 89 + -39

Combine like terms: 89 + -39 = 50
-5x = 50

Divide each side by '-5'.
x = -10

Simplifying
x = -10

See similar equations:

| 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) | | x-3x+5=3x-0.5 | | 2x+3*2=5x+4 | | x-3x+5=3x-1 | | 5m(2m^2-n^3)= | | (5n-18)+(2n+12)=180 | | 3+5x=x+15 | | (4x-1)(x-9)=0 | | -3(m+4)=4 | | y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 | | 3.91x+16=15.2881+4x | | 3cosx=8-4secx |

Equations solver categories